2007
DOI: 10.1152/ajpregu.00227.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal antioxidant prevents adult hypertension, vascular dysfunction, and microvascular rarefaction associated with in utero exposure to a low-protein diet

Abstract: Nuyt AM. Antenatal antioxidant prevents adult hypertension, vascular dysfunction, and microvascular rarefaction associated with in utero exposure to a low-protein diet. Am J Physiol Regul Integr Comp Physiol 292: R1236 -R1245, 2007. First published November 30, 2006; doi:10.1152/ajpregu.00227.2006.-Developmental programming of hypertension is associated with vascular dysfunction characterized by impaired vasodilatation to nitric oxide, exaggerated vasoconstriction to ANG II, and microvascular rarefaction app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 85 publications
(106 reference statements)
11
161
0
6
Order By: Relevance
“…Это было подтверждено в экспериментах на кры-сах, получавших корм с низким содержанием бел-ка; их потомство имело артериальную гипертонию [71]. Добавление в пищу таким крысам антиокси-дантов (N-ацетилцистеина) предотвращало развитие гипертензии у потомства [71].…”
Section: роль оксидативного стресса как эпигенетического фактораunclassified
See 1 more Smart Citation
“…Это было подтверждено в экспериментах на кры-сах, получавших корм с низким содержанием бел-ка; их потомство имело артериальную гипертонию [71]. Добавление в пищу таким крысам антиокси-дантов (N-ацетилцистеина) предотвращало развитие гипертензии у потомства [71].…”
Section: роль оксидативного стресса как эпигенетического фактораunclassified
“…Добавление в пищу таким крысам антиокси-дантов (N-ацетилцистеина) предотвращало развитие гипертензии у потомства [71]. Напротив, добавле-ние в корм беременным крысам кортикостероидов (дексаметазона) увеличивало продукцию активных соединений кислорода [72].…”
Section: роль оксидативного стресса как эпигенетического фактораunclassified
“…88 We have also shown that antioxidant supplementation in dams fed a low-protein diet prevents low glutathione levels, hypertension, and vascular dysfunction in the offspring. 109 These observations are particularly important considering that an oxidized redox state, oxidative stress, and low-grade inflammation all contribute to the pathogenesis of chronic disorders, such as hypertension, cardiovascular and kidney diseases, and type 2 diabetes mellitus 110,111 ; in this way, it is possible that these processes may enhance significantly the risk of chronic disease in neonates born preterm.…”
Section: Inflammationmentioning
confidence: 99%
“…programming might strongly affect organ development and function [15][16][17] and GK rats present deficient beta cell mass from fetal life onwards [10,11]. Rat islet endothelial proliferation is very high around birth but declines rapidly during the first week postpartum [12].…”
Section: Deficient Islet Vascularisation In Gk Fetuses and Neonates Amentioning
confidence: 99%
“…Indeed, vessel development, a major component of pancreatic islet development and function, is particularly active around birth [12][13][14] and altered programming of vascularisation has been shown to affect the development and function of various organs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%